PERILAKU KOMUNIKASI PENGGUNAAN MEDIA SOSIAL TIKTOK DI KALANGAN MAHASISWA KPI FAKULTAS DAKWAH DAN KOMUNIKASI UNIVERSITAS ISLAM NEGERI SUMATERA UTARA STAMBUK 2019 - Sulistia, Dirga Ayu; Simamora, Irma Yusriani (Jurnal Indonesia : Manajemen Informatika dan Komunikasi, 2023)
This study discusses the communication behavior of TikTok social Network users among the students of the Islamic Broadcasting and Media Studies (KPI) program at the Faculty of Dakwah, Islamic State University of North Sumatra, course 2019. This study aims to find out how the student KPI's communication behavior of class 2019 via social Network TikTok. The research method used is qualitative with a descriptive approach. The researcher used observational tools, interview guide and himself as the main tools. Research data was collected through in-depth interviews with KPI students and analysis was performed holistically for a comprehensive understanding of the use of TikTok in the context of student-to-student communication. Research results show that KPI students, as users of the social Network TikTok, use the platform as a means of entertainment, a source of knowledge, learning about Islam, and a motivation to share. their own positive content. TikTok's social media also makes it easy for them to stay up to date with relevant trending information. In addition, students' communication behavior when using TikTok tends to be positive and has no negative impact. However, we are reminded to use this platform wisely, avoid abuse, and always categorize trending information and content seriously and intelligently. This study provides valuable insights into TikTok's social media usage among KPI students and its relevance in digital communication in the context of higher education.